Depletion of Neutrophils Promotes the Resolution of Pulmonary Inflammation and Fibrosisin Mice Infected with Paracoccidioides brasiliensis (2016)
ABSTRACT: Chronic stages of paracoccidioidomycosis (PCM) are characterized by granulomatous lesions which promote the development of pulmonary fibrosis leading to the loss of respiratory function in 50% of patients; in addition, it has been observed that neutrophils predominate during these chronic stages of P. brasiliensis infection. The goal of this study was to evaluate the role of the neutrophil during the chronic stages of experimental pulmonary PCM and during the fibrosis development and tissue repair using a monoclonal specific to this phagocytic cell. Male BALB/c mice were inoculated intranasally with 1.5x106 P. brasiliensis yeast cells. A monoclonal antibody specific to neutrophils was administered at 4 weeks post-inoculation followed by doses every 48h during two weeks. Mice were sacrificed at 8 and 12 weeks post-inoculation to assess cellularity, fungal load, cytokine/chemokine levels, histopathological analysis, collagen and expression of genes related to fibrosis development. Depletion of neutrophils was associated with a significant decrease in the number of eosinophils, dendritic cells, B cells, CD4-T cells, MDSCs and Treg cells, fungal load and levels of most of the pro-inflammatory cytokines/chemokines evaluated, including IL-17, TNF-α and TGF-β1. Recovery of lung architecture was also associated with reduced levels of collagen, high expression of TGF-β3, matrix metalloproteinase (MMP)-12 and -14, and decreased expression of tissue inhibitor metalloproteinase (TIMP)-2, and MMP-8. Depletion of neutrophils might attenuate lung fibrosis and inflammation through down-regulating TGF-β1, TNF-α, IL-17, MMP-8 and TIMP-2. These results suggest that neutrophil could be considered as a therapeutic target in pulmonary fibrosis induced by P. brasiliensis.